2016
DOI: 10.1111/famp.12229
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Research in Emotionally Focused Therapy for Couples

Abstract: Emotionally Focused Therapy for Couples (EFT) is a brief evidence-based couple therapy based in attachment theory. Since the development of EFT, efficacy and effectiveness research has accumulated to address a range of couple concerns. EFT meets or exceeds the guidelines for classification as an evidence-based couple therapy outlined for couple and family research. Furthermore, EFT researchers have examined the process of change and predictors of outcome in EFT. Future research in EFT will continue to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(109 citation statements)
references
References 63 publications
6
102
0
1
Order By: Relevance
“…Emotionally Focused Couple Therapy has a long tradition of rigorously testing clinical outcomes and processes of change associated with successful outcomes (Wiebe & Johnson, ). Process research is a vital aid to therapists understanding an approach, as clinical handbooks are rarely detailed enough to guide a therapist on all of the therapeutic tasks that facilitate change (Bradley & Johnson, ).…”
Section: Process Research In Eftmentioning
confidence: 99%
“…Emotionally Focused Couple Therapy has a long tradition of rigorously testing clinical outcomes and processes of change associated with successful outcomes (Wiebe & Johnson, ). Process research is a vital aid to therapists understanding an approach, as clinical handbooks are rarely detailed enough to guide a therapist on all of the therapeutic tasks that facilitate change (Bradley & Johnson, ).…”
Section: Process Research In Eftmentioning
confidence: 99%
“…In a narrative review, Wiebe and Johnson () identified one controlled and two uncontrolled trials which evaluated the effects of emotionally focused couple therapy on post‐traumatic symptoms and relationship distress. In the controlled trial which involved couples in which one partner had post‐traumatic symptoms arising from child sexual abuse, Dalton et al .…”
Section: Disorders Where Anxiety Is a Central Featurementioning
confidence: 99%
“…Some have claimed EFT to be the most researched and most effective couple's therapy Wiebe and Johnson, 2016), with 10 sessions of EFT improving dyadic adjustment of the relationship, and others regard it as a form of exposure therapy, exposing the couples to experiences that are emotionally taxing within the relationship (Greenman and Johnson, 2013). A few sessions of EFT have also been found to elicit greater emotional dependency on the partner (allowing to "distribute" the risk), as handholding after EFT reduced the stress experienced after electric shock through Coan et al's (2006) handholding paradigm .…”
Section: Application Of Co-thermoregulation Into Current Therapiesmentioning
confidence: 99%